Usefulness of magnifying endoscopy with narrow-band imaging for determining gastric tumor margin - Kiyotoki, Shu; Nishikawa, Jun; Satake, Masaaki; Fukagawa, Yuki; Shirai, Yasuyuki; Hamabe, Kouichi; Saito, Mari; Okamoto, Takeshi; Sakaida, Isao (Journal of gastroenterology and hepatology, 2010)
Background and Aim:  Magnifying endoscopy with narrow‐band imaging (ME‐NBI) enhances images of the irregular mucosal structures and microvessels of gastric carcinoma, and could be useful for determining the margin between cancerous and non‐cancerous mucosa. We evaluated the usefulness of ME‐NBI for determining the tumor margin compared with indigocarmine chromoendoscopy (ICC). Methods:  The subjects were 110 patients (with 118 lesions) who underwent endoscopic submucosal dissection for gastric tumors. They were randomized into ME‐NBI and ICC groups. Marking was carried out by electrocautery with the tip of a high‐frequency snare at the tumor margins determined by each observation. The distance from the marking dots to the tumor margin was measured histopathologically in the resected specimens. Marking was diagnosed as accurate if the distance was less than 1 mm. Results:  Of the 118 gastric lesions, 55 were allocated to the ME‐NBI group, and 63 to the ICC group. Seventeen lesions in the ME‐NBI group and 18 lesions in the ICC group were excluded because the distance from the marking dots to the tumor margin was immeasurable histopathologically. Thirty‐eight lesions in the ME‐NBI group and 45 lesions in the ICC group were evaluated. The rate of accurate marking of the ME‐NBI group was significantly higher than that of the ICC group (97.4% vs 77.8%, respectively; P‐value = 0.009). Conclusion:  Magnifying endoscopy with narrow‐band imaging can identify gastric tumor margins more clearly than ICC.